DISTINCTIVE MORPHOMETRIC TRAITS AMONG THREE POPULATIONS OF KEMIRI SUNAN (Reutealis trisperma) AS VARIETY CANDITATES - - Dani; - Syafaruddin; - H. Supriadi (Pusbindiklat - LIPI, 2012)
Kemiri sunan (Reutealis trisperma) is a potential tree plant for biodiesel source. However, information related to phenotypic and genotypic variabilities of intra- and inter-populations is very lacking. This work aims to identify morphometric traits which show any differences among three populations of kemiri sunan as variety candidates, i.e. Banyuresmi, Cinunuk, and Padahanten. Thirty mature leafs and 30 normal seeds were randomly collected from each population. Morphometric characters observed were length and width of leaf, length and width of seed, seed weight, and kernel weight. Analysis of variance showed a high significant (p ≤ 0.01) in inter-populations differences for almost all characters observed, except for seed weight character. Leaf width has high value of broad sense heritability (H2), so that it should be used as the most valuable character for distinguishing among the three populations of kemiri sunan. Based on dissimilarity matrices analysis, Padahanten population showed the highest dissimilarity.